2022
DOI: 10.1038/s41368-022-00187-z
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes rewire the cartilage microenvironment in osteoarthritis: from intercellular communication to therapeutic strategies

Abstract: Osteoarthritis (OA) is a prevalent degenerative joint disease characterized by cartilage loss and accounts for a major source of pain and disability worldwide. However, effective strategies for cartilage repair are lacking, and patients with advanced OA usually need joint replacement. Better comprehending OA pathogenesis may lead to transformative therapeutics. Recently studies have reported that exosomes act as a new means of cell-to-cell communication by delivering multiple bioactive molecules to create a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 174 publications
0
30
0
Order By: Relevance
“…It was shown that miR-21-5, as a lead cardioactive MSC-exosomal-microRNA, mediated effects on increasing engineered cardiac tissues contractility and was suggested as a specific molecular target for optimizing cardio-therapies (Mayourian et al, 2018). In recent years, increasing studies have been conducted on the application of exosomes in the treatment of neurological diseases (Budden et al, 2021;Xu et al, 2017;Rufino-Ramos et al, 2017). More attention should also be paid to bottlenecks in exosome treatment, including the limitation of increasing exosome production, the difficulty of analyzing the effective components of exosomes and the better improvement of the functions of the active component.…”
Section: Characteristics Of Exosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that miR-21-5, as a lead cardioactive MSC-exosomal-microRNA, mediated effects on increasing engineered cardiac tissues contractility and was suggested as a specific molecular target for optimizing cardio-therapies (Mayourian et al, 2018). In recent years, increasing studies have been conducted on the application of exosomes in the treatment of neurological diseases (Budden et al, 2021;Xu et al, 2017;Rufino-Ramos et al, 2017). More attention should also be paid to bottlenecks in exosome treatment, including the limitation of increasing exosome production, the difficulty of analyzing the effective components of exosomes and the better improvement of the functions of the active component.…”
Section: Characteristics Of Exosomesmentioning
confidence: 99%
“…The crosstalk between the cartilage and subchondral bone is proceeding in an orderly manner, conducted in an exosome-dependent pattern (Domenis et al, 2017). Once the balance of the interaction is disrupted, cartilage breaks down and subchondral bone remodels abnormally, exacerbating the progression of OA (Wu et al, 2022). TMJ is one of the most flexible joints in the body and the subchondral bone of TMJ has an outstanding ability to withstand multidirectional forces.…”
Section: Subchondral Osteocytes-derived Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…58,59 However, most studies have focused on the RNA and protein content of EVs, while little has been reported on the DNA carried within them. [60][61][62][63] Takahashi et al showed that EVs maintain cellular homeostasis and prevent aberrant activation of the innate immune response by expelling damaged DNA from cells, and when this process is impaired, the DNA they carry can activate inflammatory factors including the cGAS-STING pathway and the AIM2 inflammasome. 64 In the study of the gastrointestinal response to the chemotherapeutic agent irinotecan, Lian et al found that chemotherapy-induced the release of large amounts of double-stranded DNA from exosomes in the gastrointestinal tract, and this "auto-DNA" entered the cytoplasm of innate immune cells and activated AIM2 inflammasome.…”
Section: Extracellular Vesicles -Aim2mentioning
confidence: 99%
“…These membranous exosomes contain proteins, mRNA, DNA, miRNA, lipids, and other molecules from the cytoplasm of their parent cell (Figure 1). In addition, multivesicular bodies can be sent to lysosomes from degradation or fuse with the plasma membrane and release exosomes via exocytosis (14). A variety of cell types secrete exosomes.…”
Section: Exosomes Biogenesis and Releasementioning
confidence: 99%